2012
DOI: 10.5999/aps.2012.39.5.452
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Phosphatidylcholine and Deoxycholate Compound Injections to the Localized Adipose Tissue: An Experimental Study with a Murine Model

Abstract: BackgroundPhosphatidylcholine (PPC) and deoxycholate (DCA) compound has been recently used for the purpose of partial lipolysis and is valued for its efficacy and lower invasiveness compared to liposuction and dermolipectomy used previously. In this article, the authors discuss the efficacy of the PPC dissolved in DCA via an experimental rat study model, along with suggesting a useful animal experimental model for the study of adipose tissue and lipolysis.MethodsBilateral inguinal fat pads of an experimental r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 21 publications
0
14
0
2
Order By: Relevance
“…For instance, Lee et al demonstrated the prophylactic administration of PC for 12 weeks in HFD fed mice alleviated HFD induced increases in body weight, mesenteric fat mass, triglyceride and total cholesterol levels [ 17 ]. In the clinical practice, lecithin/DC injections (Lipostablil or Lipodissolve) have been used locally to decrease fat deposits [ 72 , 73 , 74 ], attributed to the lysis of adipose cells. However, such lysis is not cell-selective, thus LipoDissolve induces significant side effects of inflammatory responses and neuronal damage [ 64 , 74 , 75 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Lee et al demonstrated the prophylactic administration of PC for 12 weeks in HFD fed mice alleviated HFD induced increases in body weight, mesenteric fat mass, triglyceride and total cholesterol levels [ 17 ]. In the clinical practice, lecithin/DC injections (Lipostablil or Lipodissolve) have been used locally to decrease fat deposits [ 72 , 73 , 74 ], attributed to the lysis of adipose cells. However, such lysis is not cell-selective, thus LipoDissolve induces significant side effects of inflammatory responses and neuronal damage [ 64 , 74 , 75 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…The latter have been investigated for the reduction of subcutaneous fat in small studies [9–16], but no injectable pharmacologic treatment is currently licensed for the reduction of SMF. Overall, robust clinical evidence regarding the efficacy and safety of nonsurgical methods for the reduction of SMF is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Each parameter was assigned a score 1 through 4 per microscopic field (100Â) whereby grade 1 (<25%), grade 2 (26-50%), grade 3 (51-75%), and grade 4 (>76%) (Noh and Heo, 2012;Rittes et al, 2006).…”
Section: Experimental Protocolmentioning
confidence: 99%